1998
DOI: 10.1007/s002210050380
|View full text |Cite
|
Sign up to set email alerts
|

Scaling anticipatory postural adjustments dependent on confidence of load estimation in a bi-manual whole-body lifting task

Abstract: Anticipatory control of motor output enables fast and fluent execution of movement. This applies also to motor tasks in which the performance of movement brings about a disturbance to balance that is not completely predictable. For example, in bi-manual lifting the pick-up of a load causes a forward shift of the centre of mass with consequent disturbance of posture. Anticipatory postural adjustments are scaled to the expected magnitude of the perturbation and are initiated well before the availability of senso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0
4

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 31 publications
1
28
0
4
Order By: Relevance
“…Gait initiation, rising on tiptoes (Crenna and Frigo 1991), whole-body lifting (Stapley et al 1998;Toussaint et al 1998), or releasing a load from extended arms (Aruin and Latash 1996) are other tasks that probably start with an A-eigenmovement causing a forward CG acceleration. The goal achieved by the A-eigenmovement is however dierent according to the task: in gait initiation, rising on tiptoes, and whole-body lifting, it mainly shifts the CG forward, whereas in load release, as in trunk bending, it mainly reduces the equilibrium disturbance initiated by the prime movement, due to the dynamic interactions between segments.…”
Section: Discussionmentioning
confidence: 99%
“…Gait initiation, rising on tiptoes (Crenna and Frigo 1991), whole-body lifting (Stapley et al 1998;Toussaint et al 1998), or releasing a load from extended arms (Aruin and Latash 1996) are other tasks that probably start with an A-eigenmovement causing a forward CG acceleration. The goal achieved by the A-eigenmovement is however dierent according to the task: in gait initiation, rising on tiptoes, and whole-body lifting, it mainly shifts the CG forward, whereas in load release, as in trunk bending, it mainly reduces the equilibrium disturbance initiated by the prime movement, due to the dynamic interactions between segments.…”
Section: Discussionmentioning
confidence: 99%
“…Unexpected sudden loading and unloading of the trunk have been considered as challenges to trunk muscle control (Toussaint et al 1998, Cholewicki et al 2000 Burg and van Diee¨n 2001, Moseley et al 2003, Lee et al 2011. Inadequate responses to the perturbation are considered to be a risk factor for low-back injury , Cholewicki et al 2005.…”
Section: Introductionmentioning
confidence: 99%
“…In novel objects of unknown weight, lift and grip forces stabilize at a new level within two or three trials (Gordon et al 1993). In addition, Toussaint et al (1998) found anticipatory postural adjustments in whole-body lifting movements to be adapted to new loads within four trials. Thus, the programming of parameters concerning the expected forces is updated quite fast.…”
Section: Discussionmentioning
confidence: 96%